A qualidade requerida da educação profissional técnica denível médio - Fabiana Sabara Dias (2011)
The present dissertation brings up a critical and analytical investigation of how to achieve social quality in secondary schools Professional Technical Education, based on the following questioning: which social quality indicators are needed to consolidate the democratic principles as the basis of secondary schools Professional Technical Education? As a means of answering this question, it was chosen as the investigations starting point the building up of a methodological process in which the problem to be investigated and its delimitation are presented. The basis for this investigative work were a relational analysis of theoretical studies which criticize or give alternatives to the politics/restructuring applied to secondary schools Professional Technical Education from 1990 up to 2010 and secondary schools Professional Technical Education programs political and pedagogical restructuring propositions presented in official and legal documents. The methodological resources used to collect data were: the in depth questionnaire, which was answered by eleven researchers of national prominence in the field of Professional Technical Education, and the documentary research. The examination of the data collected from the questionnaires was based on content analysis. The documentary analysis consisted on the examination of the official texts related to public policies concerning secondary schools Professional Technical Education. These texts were also used to support the bibliographic researchs development. The general aim of this dissertation is to describe and analyze social quality indicators and parameters relevant to secondary schools Professional Technical Education, which are presented and/or hidden in theoretical and critical, official and legal texts facing the political and pedagogical (re)structuring of secondary schools Professional Technical Education. Everything as a means of identifying evidences and/or negations of the (re)signifying of the binomial schooling and professional technical preparing to work. Using a qualitative approach, one seeks to comprehend the quality socially relevant to Professional Technical Education and to report understandings concerning the interrelations between the world of work and the broader world of social relations. The interrelations between the Professional Technical Education field and the subjects who build this education up are also considered. Based on this analysis, this dissertation brings up social quality dimensions and indicators considered as a primary provocation of a process that involves broader and constant discussions necessary to actualize Professional Technical Educations social quality in Brazil